THE EFFECT OF ENTREPRENEURIAL ORIENTATION AND PRODUCT INNOVATION ON MARKETING PERFORMANCE MSME IN VILLAGE PACKAGING REGENCY SIDOARJO - Mega D. Novita; Soesanto Soesanto (SEAN Institute, 2022)
Study This aim For know And analyze influence Entrepreneurial Orientation and Product Innovation towards MSMEs Performance in Villages Sidoarjo District Packaging. This research uses a type of quantitative method. Study This use data primary And secondary Where method collection use questionnaire. Population in study This is perpetrator MSMEs in Village Packaging Regency Sidoarjo amount 35 person. Study This will describe about connection because consequence, so that method This use sample And hypothesis. The data instrument test used in this study is the validity test, reliability test. The technical analysis in this study is linear regression analysis double, coefficient determination (r 2 ) and test hypothesis use test t, And test f. Results from study This in get from analysis regression linear double is Y = 2.878 + 0.375 X1 + 0.253 X2 + 0.563 X3 + e. The t test shows probability significance < 0.05 Which show variable Orientation Entrepreneurship (X 1 ) And Innovation Product (X 2 ) influential significant to MSME Performance in Packaging Village, Sidoarjo Regency. The value of the F test has a value probability significance as big 0.000 < 0.05, Where variable Orientation Entrepreneurship (X 1 ) and Product Innovation (X 2 ) are equally influential significant to Performance MSMEs in Village Packaging Regency Sidoarjo (Y). Conclusion in research This is variable free Orientation Entrepreneurship (X 1 ) And Innovation Product (X 2 ) influential significant to variable bound Performance MSMEs in Village Packaging Regency Sidoarjo (Y). So that hypothesis in research This accepted.